2019
DOI: 10.1186/s12941-019-0303-3
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus agalactiae from Ethiopian pregnant women; prevalence, associated factors and antimicrobial resistance: alarming for prophylaxis

Abstract: BackgroundMaternal Streptococcus agalactiae (Group B Streptococcus, GBS) colonization rates and its antibiotic resistance patterns provide important information useful in guiding prevention strategies. There is a paucity of evidence about GBS in the Amhara National Regional State, Ethiopia.ObjectiveTo determine colonization prevalence, associated risk factors, and antibiotics resistance including inducible clindamycin resistance patterns of GBS among Ethiopian pregnant women.MethodsA prospective cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
41
4
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 37 publications
19
41
4
2
Order By: Relevance
“…However, our results agree with recent ndings in Ethiopia were a resistance of 77.3% to penicillin G was reported in pregnant women (17). Other studies have reported resistance to both penicillin G and ampicillin of 10.2% and 9.2% as well as 19.5% and 14.6% respectively (18,19). The high resistance reported may be due to the wide and non-prescription use of these two drugs in our study area (47,49).…”
Section: Multi-drug Resistancesupporting
confidence: 92%
See 2 more Smart Citations
“…However, our results agree with recent ndings in Ethiopia were a resistance of 77.3% to penicillin G was reported in pregnant women (17). Other studies have reported resistance to both penicillin G and ampicillin of 10.2% and 9.2% as well as 19.5% and 14.6% respectively (18,19). The high resistance reported may be due to the wide and non-prescription use of these two drugs in our study area (47,49).…”
Section: Multi-drug Resistancesupporting
confidence: 92%
“…This study also reports resistance to other penicillin surrogates (50) such as ceftriaxone 46.5% (20/43) and cefazolin 72.1% (31/43). A similar observation of approximately 31% for ceftriaxone was reported (18,51), whilst a lower range of 0%-15% for cefazolin has been reported (51)(52)(53). We recommend that antibiotic susceptibility testing should be performed if penicillin G or ampicillin therapy is needed in the prevention of neonatal GBS infection.…”
Section: Multi-drug Resistancesupporting
confidence: 57%
See 1 more Smart Citation
“…Primary studies conducted in the East African countries showed the colonization rates ranged from 3.0% to 28.8% [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]; Central Africa,20.0% [27,28]; Western Africa, 2.5% to 34.2% [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]; Southern Africa, 1.77% to 48.23% [49][50][51][52][53][54][55][56][57]…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies identified various risk factors for GBS colonisation during pregnancy. These include obesity, age, being African‐American or Caucasian, older age at the first pregnancy, a history of GBS during a previous pregnancy, being multigravida, meconium‐stained amniotic fluid, a longer duration of the premature rupture of membranes, and smoking . The study by Chen et al builds on the existing literature and sets the stage for additional, much‐needed work to examine the factors associated with GBS colonisation during pregnancy, study causality and interrogate underlying mechanisms.…”
mentioning
confidence: 99%